Assessment and Treatment of Problem Behavior Maintained by Termination of Interruptions. (3rd April 2019) - Cariveau, Tom; Miller, Sarah J.; Call, Nathan A.; Alvarez, Jessica
ABSTRACT: Purpose: Previous research has identified termination of interruptions to repetitive behaviour as a reinforcer capable of maintaining problem behaviour. Effective treatments have included functional communication training and multiple schedules of reinforcement. Methods: In the present study, a functional analysis determined that the aggression of an eight-year-old boy with autism spectrum disorder was maintained by termination of interruptions of repetitive behaviour. An intervention was implemented consisting of differential reinforcement of other behaviour and response cost. Results: The intervention produced and maintained a reduction in aggression and increased tolerance for interruptions of systematically increasing durations. Conclusions: This case study demonstrates an alternative approach to the treatment of problem behaviours such as aggression maintained by termination of repetitive behaviour that includes teaching the individual to tolerate interruption of repetitive behavior.